Investigation to the influence of additional magnets positions on four-magnet bi-stable piezoelectric energy harvester - Li, Xinxin; Huang, Kexue; Li, Zhilin; Xiang, Jiangshu; Huang, Zhenfeng; Mao, Hanling; Cao, Yadong (Bulletin of the Polish Academy of Sciences. Technical sciences, 2022)
Although the study of oscillatory motion has a long history, going back four centuries, it is still an active subject of scientific research. In this review paper prospective research directions in the field of mechanical vibrations were pointed out. Four groups of important issues in which advanced research is conducted were discussed. The first are energy harvester devices, thanks to which we can obtain or save significant amounts of energy, and thus reduce the amount of greenhouse gases. The next discussed issue helps in the design of structures using vibrations and describes the algorithms that allow to identify and search for optimal parameters for the devices being developed. The next section describes vibration in multi-body systems and modal analysis, which are key to understanding the phenomena in vibrating machines. The last part describes the properties of granulated materials from which modern, intelligent vacuum-packed particles are made. They are used, for example, as intelligent vibration damping devices.